Effects of population mobility on the COVID-19 spread in Brazil. - Eduarda T C Chagas; Pedro H Barros; Isadora Cardoso-Pereira; Igor V Ponte; Pablo Ximenes; Flávio Figueiredo; Fabricio Murai; Ana Paula Couto da Silva; Jussara M Almeida; Antonio A F Loureiro; Heitor S Ramos (PLoS ONE, 2021)
This article proposes a study of the SARS-CoV-2 virus spread and the efficacy of public policies in Brazil. Using both aggregated (from large Internet companies) and fine-grained (from Departments of Motor Vehicles) mobility data sources, our work sheds light on the effect of mobility on the pandemic situation in the Brazilian territory. Our main contribution is to show how mobility data, particularly fine-grained ones, can offer valuable insights into virus propagation. For this, we propose a modification in the SENUR model to add mobility information, evaluating different data availability scenarios (different information granularities), and finally, we carry out simulations to evaluate possible public policies. In particular, we conduct a case study that shows, through simulations of hypothetical scenarios, that the contagion curve in several Brazilian cities could have been milder if the government had imposed mobility restrictions soon after reporting the first case. Our results also show that if the government had not taken any action and the only safety measure taken was the population's voluntary isolation (out of fear), the time until the contagion peak for the first wave would have been postponed, but its value would more than double.